2013
DOI: 10.1080/02786826.2012.724186
|View full text |Cite
|
Sign up to set email alerts
|

A Multidomain Magnetic Passive Aerosol Sampler: Development and Experimental Evaluation

Abstract: An innovative "quarter-sized" multidomain magnetic passive aerosol sampler (MPAS) has been developed, mainly for determining particle penetration through personal protective ensembles. The MPAS is a 28 mm disc with a height of 8.6 mm. It consists of 186 small magnets with about 140 on the collection area, arranged in an alternating N and S pole pattern. In contrast to conventional passive samplers, it uses magnetic force to collect a quantifiable amount of surrogate Fe 3 O 4 particles within a substantially sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In a magnetic collector, particles are separated based on both their size and magnetic susceptibility, simultaneously. 16,17 A recent example of the development of a passive aerosol sampler using permanent magnets was reported by Hsiao et al 23 The sampler used 186 small magnets arranged in an alternating pole configuration to collect particles as they deposited onto the collection substrate though no collection efficiency data were reported. 23 An active aerosol sampler designed using a 3-stage high-gradient permanent magnetic separation (HGPMS) array was first reported by Cheng et al 16 The authors demonstrated the effective capture of nanoparticles by configuring the permanent magnets as reversed pole pairs and adding a paramagnetic matrix such as stainless-steel wool to create the high-gradient magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…In a magnetic collector, particles are separated based on both their size and magnetic susceptibility, simultaneously. 16,17 A recent example of the development of a passive aerosol sampler using permanent magnets was reported by Hsiao et al 23 The sampler used 186 small magnets arranged in an alternating pole configuration to collect particles as they deposited onto the collection substrate though no collection efficiency data were reported. 23 An active aerosol sampler designed using a 3-stage high-gradient permanent magnetic separation (HGPMS) array was first reported by Cheng et al 16 The authors demonstrated the effective capture of nanoparticles by configuring the permanent magnets as reversed pole pairs and adding a paramagnetic matrix such as stainless-steel wool to create the high-gradient magnetic field.…”
Section: Introductionmentioning
confidence: 99%